2019
DOI: 10.3389/fimmu.2019.02970
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of CCR7 and CXCR4 During B Cell Development Controls CXCR4 Responsiveness and Bone Marrow Homing

Abstract: The CXCL12-CXCR4 axis plays a key role in the retention of stem cells and progenitors in dedicated bone marrow niches. It is well-known that CXCR4 responsiveness in B lymphocytes decreases dramatically during the final stages of their development in the bone marrow. However, the molecular mechanism underlying this regulation and whether it plays a role in B-cell homeostasis remain unknown. In the present study, we show that the differentiation of pre-B cells into immature and mature B cells is accompanied by m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…As previously described, Il4ra promotes B cell autophagy required for memory maintenance and antigen presentation [ 33 ]. In contrast, Cxcr4 signaling is uniquely activated in the functional state of limb muscle B cells demonstrating the differentiation of these cells into plasma cells [ 46 ]. While B cells lose their responsiveness to Cxcl12, the cognate ligand of Cxcr4, during development, they regain their sensitivity upon differentiation into mature B cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, Il4ra promotes B cell autophagy required for memory maintenance and antigen presentation [ 33 ]. In contrast, Cxcr4 signaling is uniquely activated in the functional state of limb muscle B cells demonstrating the differentiation of these cells into plasma cells [ 46 ]. While B cells lose their responsiveness to Cxcl12, the cognate ligand of Cxcr4, during development, they regain their sensitivity upon differentiation into mature B cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent data show that tumor B and plasma cells may exert both pro-tumor and anti-tumor effects depending on the TME, phenotypes of B cells and the relative antibodies production. CXCR4 is expressed at all stages of B cell development in BM from HSCs to mature B cells and plays a major role in the homing of B cell precursors ( 108 ). CXCR4 is necessary for developing B cells in the BM but not for mature B cells ( 109 ).…”
Section: Cxcr4 and Cxcr7 In B Cellsmentioning
confidence: 99%
“…In this regard, a recent study by S. McHeik et al. demonstrated that expression of CCR7 in B cells selectively inactivated CXCR4, impairing migration towards its ligand CXCL12, and facilitating emigration from BM to PB ( 114 ). Mechanistically, up-regulation of CCR7 favors the formation of CXCR4-CCR7 heterodimers, thus acting as a selective endogenous allosteric modulator of CXCR4 that impairs its ability to activate certain G-protein complexes.…”
Section: Cllmentioning
confidence: 99%
“…On the other hand, CXCR4 might promote LN homing in an indirect manner, for example, favoring relocation of CLL from BM to the LN. In this respect, up-regulation of CCR7 in normal B cells selectively inactivates CXCR4 whereas mature B cells from CCR7 -/- mice display higher responsiveness to CXCL12 and improved retention in the BM ( 114 ). Accordingly, CXCR4 is the main receptor driving homing of CLL cells to BM where stromal cells provide protection from spontaneous or drug-induced apoptosis ( 51 , 113 , 137 ).…”
Section: Cllmentioning
confidence: 99%